Relationship of Parameter for Stiffness and Strength Based In-Place Evaluation of Control Compacted Unbound Materials of Pavement Materials in Highway Construction - น้อยก้อน, ณัฐกฤษ (SAU JOURNAL OF SCIENCE & TECHNOLOGY, 2019)
This paper presents the determination of stiffness and strenght of compacted pavement materials in highway construction. The soil tests were analyzed both control compacted soil in the field (control compaction test) and based in-place evaluation (field test). The testing apparatuses were applied by Soil Stiffness Gauge (SSG), Dynamic Cone Penetrometer (DCP) and Nuclear Density Gauge. This paper presents stiffness and strength based methods for rapid in-place monitoring compaction quality control during highway construction. Then analysis the deviation of soil tests between good controlling in compaction (control compaction test) and generally compacted soil in field (field test). The compacting energy and soil moisture content were under controlled. Results Then the tests from SSG and DCP for construction quality control compaction and field provide nearby in result. However, the deviation of soil test from SSG and DCP testing in construction quality control compaction soil are less than in the field. The results of this study, there exists a discernable correlation elastic modulus as measured and control compacted soil in the field by the SSG, DCP and found that elastic modulus (ESSG) relationship with CBR by direct variation. In particular, Field tests also indicated ESSG = 5.23CBR1.093. Relationships between Field CBR (CBRfield) and DCP in test box (CBRDCP) of total materials the found that with direct variation. In addition mean, CBRfield(control) = 3.072CBRDCP – 43.88. Indicated these methods exhibited good potential for construction quality control as well as the development of performance-based specifications in Thailand.